Oxford Word Skills upper-intermediate-Advanced vocabulary : learn to use the most important words and phrases in English topic by topic - Gairns, Ruth, ....-; Redman, Stuart, 1950- (Oxford : Oxford University Press, 2020)
Learn to use the most important words and phrases in English topic by topic. Oxford Word Skills teaches yoy the words and phrases you need to use in English in real life.
Keywords: English language; Vocabulary